Faith beyond Belief : Spirituality for Our Times; A Conversation - Grün, Anselm; Steindl-Rast, David (Book collections on Project MUSE., 2016)
A personal, surprising, and heart-warming book wherein two spiritual masters of our time advance the central questions of life and faith.